Who Controls the Budget : The Legislature or the Executive? - Lienert, Ian (IMF Working Papers; Working Paper ;, 2005)
Country-specific factors prevent a strong linear relationship between the legislature's budgetary powers and the extent of its separation from the executive. Electoral and voting systems, bicameralism, constitutional and legal constraints, voluntary contracts of political parties, and long-standing traditions all influence the relative budgetary powers of executives and legislatures. Differences in the legislature's budgetary authority in twenty-eight countries with five different forms of government are examined. It is concluded that differences in budgetary powers within a particular form of government are as great as those between different forms of government.